Efeitos da administração crônica do extrato de casca de uva em camundongos submetidos a um modelo progressivo da Doença de Parkinson - Macedo, Amanda Maria de [UNIFESP] (2020)
Parkinson's disease (PD) is a neurodegenerative disease affecting mainly the elderly population. PD etiology remains unknown, however, evidence shows that genetic predisposition and environmental factors, such as contamination by heavy metals and pesticides, are important factors for the emergence of PD. Currently, the development of new drugs to treat PD is a challenge. The antiparkinsonian drugs used in the clinic do not prevent disease progression and cause side effects. In this context, previous studies have shown that substances with antioxidant and anti-inflammatory activities have neuroprotective effect in PD. In this sense, the aim of this study was to investigate the effect of Vitis labrusca grape skin extract (UVA) on mice submitted to the progressive parkinsonism model induced by repeated administration of reserpine (RES). For this study, male Swiss mice (6-7 months) were used and three experiments were carried out. This study was approved by CEUA No. 8979280616. The animals were treated daily with UVA (16, 160 or 2400 mg/kg; orally) and every 48 h with RES (0.1 mg/kg, subcutaneously for 30 days). Sensory (olfactory discrimination), motor (catalepsy, oral movements, open field, and rotarod test) and cognitive (recognition of the novel object) evaluations were conducted across the treatment. At the end of the experimental protocol, the animals were euthanized and the brains were collected and stored. Our main results showed that the chronic treatment with UVA decreased the time of catalepsy, reduced the frequency of oral movements, restored memory deficit and decreased the frequency of falls on the rotarod. These findings showed that UVA has a neuroprotective effect in a progressive PD animal model. Finally, more studies are needed to elucidate its mechanism of action.